IECON 2019 - 45th Annual Conference of the IEEE Industrial Electronics Society 2019
DOI: 10.1109/iecon.2019.8927110
|View full text |Cite
|
Sign up to set email alerts
|

Fast Self-Tuning Decentralized Variable Frequency Optimal Controller Design for Three-Phase Embedded Grids

Abstract: In this paper, a novel approach to variable frequency optimal controller design for the application of aircraft embedded grids is presented. Aircraft power grids by industrial standards need to be able to operate across a range of frequencies. Often, these systems are controlled by active power-based controls, which are well known for being rather slow in response time. A novel method of variable frequency optimal control using H2 optimization is presented. It is shown that designing the control as such not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…However, for the LQR controller, due to that the output controller cannot be constrained, the PLL cannot be augmented in the AFE LQR controller synthesis. Therefore, for both the LQR and PI controllers in this study, and to ensure the same dynamics for each test, the PLL in both cases is designed with a bandwidth of 100 Hz, and a damping of 0.707, based on the PLL transfer functions as defined in [37]. Therefore, the PLL controller gains for the LQR and PI controller tests are Kp=0.6282,Ki=27.92.…”
Section: Simulative Analysismentioning
confidence: 99%
“…However, for the LQR controller, due to that the output controller cannot be constrained, the PLL cannot be augmented in the AFE LQR controller synthesis. Therefore, for both the LQR and PI controllers in this study, and to ensure the same dynamics for each test, the PLL in both cases is designed with a bandwidth of 100 Hz, and a damping of 0.707, based on the PLL transfer functions as defined in [37]. Therefore, the PLL controller gains for the LQR and PI controller tests are Kp=0.6282,Ki=27.92.…”
Section: Simulative Analysismentioning
confidence: 99%
“…Note additionally, that with (29) and (30) redefining the VSI state-space model, these terms must also be submitted into (22) and (23) respectively to ensure the closed loop PI controller states of the VSI are correctly modelled accounting for PLL interactions.…”
Section: B Incorporation Of Pll Interactive Behaviourmentioning
confidence: 99%
“…In addition, since the H 2 optimisation uses the whole system model for the development of decentralised controllers, each independent controller is optimised with the knowledge of every other converters closed loop dynamics, and crosscoupled interactive effects. Due to this, studies have shown that this type of controller optimisation largely counteracts coupled interactions between converters [22]. The above studies show that full decentralisation with the capability of mitigating subsystem interactions is possible, however they all assume fixed frequency operation of the grid.…”
Section: Introductionmentioning
confidence: 99%